Metabolism and disposition of lesinurad, a uric acid reabsorption inhibitor, in humans. (3rd July 2019) - Shah, Vishal; Yang, Chun; Shen, Zancong; Kerr, Bradley M.; Tieu, Kathy; Wilson, David M.; Hall, Jesse; Gillen, Michael; Lee, Caroline A.
Abstract: The objectives of this study were to determine the absolute bioavailability of lesinurad and to characterized its disposition in humans. The oral bioavailability assessment was performed using a clinical design of simultaneous dosing of a therapeutic oral dose of lesinurad with an intravenous infusion of [ 14 C]lesinurad microdose. The bioavailability of lesinurad was determined to be 100%. The disposition of lesinurad in humans involves hepatic oxidation and renal elimination following administration of oral [ 14 C]lesinurad dose. Metabolism of lesinurad occurred post-systemically with low circulating levels of metabolites <3% of total radioactivity as 74.2% of total radioactivity was attributed to lesinurad. In vitro metabolism studies identified CYP2C9 as the predominant isoform, and summation of metabolites indicated that it was responsible for ∼50% of metabolism.